2018
DOI: 10.22219/jpbi.v4i1.5181
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ perception on students’ critical thinking skills development and problems faced by students in developing their critical thinking skills

Abstract: Critical thinking emerges when learners attempt to use their background knowledge to construct meaning through interpreting, analyzing, and manipulating information in responding to a problem or a question that requires more than a single correct answer. Two factors that affect the improvement of the students’ critical thinking skills are lecturers’ activities and students’ activities. This study was a descriptive quantitative study which aimed to investigate (1) how lecturers perceive the development of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…One of the factors identified as the cause of these problems is the lecturers' perception of the development of their students' critical thinking skills. In their current study, [24] found that out of 48 lecturers spread in four different universities, there were only 32.05% of them who included critical thinking skill aspect in their evaluation sub-scale. It showed that little emphasis was put on the development of students' critical thinking skills.…”
Section: Critical Thinking Skills In Higher Educationmentioning
confidence: 58%
“…One of the factors identified as the cause of these problems is the lecturers' perception of the development of their students' critical thinking skills. In their current study, [24] found that out of 48 lecturers spread in four different universities, there were only 32.05% of them who included critical thinking skill aspect in their evaluation sub-scale. It showed that little emphasis was put on the development of students' critical thinking skills.…”
Section: Critical Thinking Skills In Higher Educationmentioning
confidence: 58%
“…The question of answer is a productive teaching approach in stimulating critical thinking (Rashid, Sumaira & Qaisar Shahzada, 2016) Learners can realize themselves whether they are lazy or diligent in reading, it is easy or difficult to understand themselves whether they are lazy or not by written teaching materials, like or dislike reading textbooks, and so on. By using the question level, critical thinking skills can be illustrated by T Santoso et al, 2018, the concept of critical thinking through answering questions is when students try to build arguments using their background by interpreting, analyzing, and responding to problems that require more than one answer ( Amin, Astuti Muh & Adiansyah, Romi, 2018).…”
Section: B Answermentioning
confidence: 99%
“…These factors, in the implementation of learning, need to be considered to optimize the empowerment of critical thinking and student metacognitive. The results of this study can be used as a basic strategy for conducting lecture development (Amin & Adiansyah, 2018;Bensley & Spero, 2014). Teachers can develop genetic lectures by innovating such as the use of collaborative learning models (Guleker, 2015), learning strategies that facilitate the development of thinking skills (Ghanizadeh, 2017), and the use of media and learning resources that are relevant to student characteristics (Duncan & Reiser, 2007;Murray-Nseula, 2011).…”
Section: Resultsmentioning
confidence: 99%